The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/1759-7714.13823
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐educated platelet SNORD55 as a potential biomarker for the early diagnosis of non‐small cell lung cancer

Abstract: Background Despite the emerging insights into many snoRNAs (small nucleolar RNAs) which are detectable in body fluids and serve as noninvasive biomarkers, few studies have previously discussed the role of snoRNAs in tumor‐educated platelets (TEPs). Herein, we systematically estimated dysregulation of snoRNAs in non‐small cell lung cancer (NSCLC) and clarified the biomarker potential of SNORD55 in platelets. Methods We compared expression of snoRNAs between NSCLC and normal tissues using SNORic datasets. Platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“… 34 SNORD63 and SNORD96A are stable in plasma and urinary sediment, and also potentially play as noninvasive early biomarkers for clear cell renal cell carcinoma. 30 Compared with normal people, downregulated tumor-educated platelets SNORD55 is significantly related to TNM stage I/II patients with lung adenocarcinoma and lung squamous cell carcinoma, 51 and increased plasma SNORD83A was related to tumor size. 52 Tumor-educated platelets SNORD55 and plasma SNORD83A can distinguish NSCLC patients, even early NSCLC from controls with sufficient specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“… 34 SNORD63 and SNORD96A are stable in plasma and urinary sediment, and also potentially play as noninvasive early biomarkers for clear cell renal cell carcinoma. 30 Compared with normal people, downregulated tumor-educated platelets SNORD55 is significantly related to TNM stage I/II patients with lung adenocarcinoma and lung squamous cell carcinoma, 51 and increased plasma SNORD83A was related to tumor size. 52 Tumor-educated platelets SNORD55 and plasma SNORD83A can distinguish NSCLC patients, even early NSCLC from controls with sufficient specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignant tumors in the world 33 . To date, there are few effective and clinically feasible methods for early diagnosis and screening of lung cancer 34–37 . Although histology and cytology are the gold standard for the diagnosis of lung cancer, patients are often in advanced stages at the time of diagnosis by histology and cytology examination.…”
Section: Discussionmentioning
confidence: 99%
“…Dong X et al used low-speed centrifugation to separate platelets from plasma and performed quantitative polymerase chain reaction (qPCR) to detect small nucleolar RNA SNORD55. 92 The results showed that, compared with healthy controls, SNORD55 in the TEP of NSCLC patients was significantly lower, especially in early-stage patients. Importantly, they verified that TEP SNORD55 can be used as a promising biomarker for NSCLC.…”
Section: Teps May Facilitate Blood-based Tumour Diagnosismentioning
confidence: 91%